2011
DOI: 10.1111/j.1440-1827.2011.02727.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of multicentric Castleman's disease with membranoproliferative glomerulonephritis type 3‐like lesion

Abstract: Renal involvement is a significant complication of multicentric Castleman's disease (MCD) and various glomerular involvements have been reported. A 45-year-old Japanese man presented with persistent proteinuria, with lymphadenopathy and hypergammaglobulinemia. He had been diagnosed 4 years previously with MCD. As his renal impairment had progressed to renal failure, he underwent a renal biopsy. Histology revealed diffuse and global membranous lesions with large and heterogeneous epimembranous deposits. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, M-CD is characterized by general lymphadenopathy, thrombocytopenia, hepatosplenomegaly, and central nerve injury (Nagai et al, 2011). Furthermore, M-CD is characterized by general lymphadenopathy, thrombocytopenia, hepatosplenomegaly, and central nerve injury (Nagai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, M-CD is characterized by general lymphadenopathy, thrombocytopenia, hepatosplenomegaly, and central nerve injury (Nagai et al, 2011). Furthermore, M-CD is characterized by general lymphadenopathy, thrombocytopenia, hepatosplenomegaly, and central nerve injury (Nagai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [7] recently reported that thrombotic microangiopathy-like lesions are the most common pathological characteristics of Castleman's disease-associated renal injury. Other groups have reported cases of Castleman's disease with mesangial proliferative glomerulonephritis [9], renal amyloidosis [10], membranous glomerulonephritis [11], membranoproliferative glomerulonephritis (MPGN) [12,13], crescentic glomerulonephritis [14], thrombotic microangiopathy [15], and interstitial nephritis [16].…”
Section: Introductionmentioning
confidence: 99%